EXPLORING VALIDITY OF CULTURALLY-RELEVANT DEMENTIA EDUCATION MATERIALS FOR THE WIND RIVER RESERVATION. (11th November 2018) - Carrico, C; McKibbin, C; Longstreth, M; Steinman, B; Cuadrado, B; Duhamel, D
Abstract: The number of aging American Indian and Alaska Native (AI/AN) individuals is increasing, and due to an increase in the longevity among AI/AN populations, an increase in the incidence of dementia can be expected. The Indian Health Service, as well as local stakeholders, have identified a need for culturally-relevant dementia education materials for AI/AN elders, family members, and caregivers. An iterative focus-group approach was initially used to inform the creation of such materials with representatives from the Wind River Reservation. Using data derived from the focus groups, the Ten Early Signs and Symptoms of Alzheimer's Disease were adapted for the people of the Wind River Reservation. To test the validity of the culturally-relevant dementia education materials, 40 AI/AN participants were asked to match the recently developed visual images and verbal messages with the original signs and symptoms. Results showed that participants were able to match the adapted and original verbal messages 44%-80% of the time, depending on the message. Participants matched the adapted image with the original verbal message correctly 6.66–68.9% of the time. These results provide important feedback regarding face validity of these new education materials. Images with low matching scores were reviewed and targeted for improvement. Images with high matching scores were examined for key elements contributing to high scores. These results and process are a unique contribution to an area of growing emphasis as culturally-relevant education materials could contribute to increased health knowledge in a rapidly aging, diverse population in the U.S. and abroad.